Leishmania antimony resistance/ susceptibility in Algerian foci - Eddaikra N; Ait-Oudhia K; Oury B; Moulti-Mati Farida; Harrat Z; Sereno D (Open Journal of Tropical Medicine - Peertechz Publications, 2017)
Algeria is one of the most endemic countries for cutaneous and visceral forms of eishmaniosis.Strikingly, with more than 21,000 annual cases of cutaneous leishmaniosis recorded in 2010, the disease has a major public health impact. For all forms of leishmaniosis, the fi rst line treatment relies on antimonial containing drug i.e.,Glucantime®, developed during the 1950's. As early as 1986, antimonial treatment failure was reported during  utaneous leishmaniosis treatment. Linked to this therapeutic failure, Leishmania strains displaying a low susceptibility towards antimonials were isolated. Nevertheless,in Algeria, antimonial formulations still remain the first line drug for all clinical forms of leishmaniosis. Therefore, an urgent need of knowledge on the baseline antimony susceptibility status of parasites strains in Algeria is required. These pieces of knowledge will shed light not only on the prevalence of antimony resistance in this area but also on underlying factors triggering this drug resistance in natural populations.Here, we performed a review of the literature on what is known about epidemiology, treatment failure,and antimony-resistance, in Algeria. We bring information on underlying mechanisms acting in antimony resistant parasites and discuss their potential to be used for diagnostic purpose. This analysis will help to set up protocols aiming at detecting antimony resistant strains in Algeria and to test the risk of transmission,two steps that are essential to define public health policy in Algeria.